Dissecting Solvent Effects on Hydrogen Bonding. Issue 30 (14th June 2022) - Meredith, Nicole Y.; Borsley, Stefan; Smolyar, Ivan V.; Nichol, Gary S.; Baker, Christopher M.; Ling, Kenneth B.; Cockroft, Scott L.
Abstract: The experimental isolation of H‐bond energetics from the typically dominant influence of the solvent remains challenging. Here we use synthetic molecular balances to quantify amine/amide H‐bonds in competitive solvents. Over 200 conformational free energy differences were determined using 24 H‐bonding balances in 9 solvents spanning a wide polarity range. The correlations between experimental interaction energies and gas‐phase computed energies exhibited wild solvent‐dependent variation. However, excellent correlations were found between the same computed energies and the experimental data following empirical dissection of solvent effects using Hunter's α/β solvation model. In addition to facilitating the direct comparison of experimental and computational data, changes in the fitted donor and acceptor constants reveal the energetics of secondary local interactions such as competing H‐bonds. Abstract : The perturbing effects of solvation obscure the energetics of H‐bonding interactions. Experimental H‐bond energies were determined in a wide range of competitive solvents using synthetic molecular balances. Dissection of the H‐bond and solvation energetics using Hunter's solvation model enabled the direct comparison of experimental and gas‐phase computational energies and the rationalization of competing secondary electrostatic interactions.